Report on proposed upgrading & new interior design scheme of Chery Center for Weng Fatt Motor Sdn Bhd at 205, Jalan Raja Permaisuri Bainum (Jalan Kampar), 30250 Ipoh, Perak / Nik Mohd Faeezul Nik Yusoff - Nik Yusoff, Nik Mohd Faeezul (Faculty of Architecture, Planning and Surveying, 2009)
The final project for Diploma in Interior Design is manifestation about the student understanding in all interior project espect that had been learn from the basic to the presentation for propose design. For the final project, the upgrading for Chery Center had been choose at 205, Jalan Raja Permaisuri Bainum (Jalan Kampar), 30250 Ipoh, Perak. With the new 3S Center, hopes that it will upgrade the images of Chery and widen the Chery market while providing a good services. The theme and the concept that will be apply on both space “interior and exterior” is to shown the esthetic value and the prestige of Chery. Several research had been done to make the project more achives for this final project, among the research include the site analysis, research method such interview the client, observing, case study and surveying. All the research been done is to identified the existing issue and problem that occur. All the information that had been gathered will be apply with the purpose to get one good design and compatible with the Chery Cooperate image, neither the function nor the esthetic value. The new approachent concept and the modern image will be apply to get new concept and image compatible and can be shown in design and merge with Chery identity.